Acceptance Analysis of Insurance E-Receipt Information System Using Technology Acceptance Model - Andrian Kurniawan Perdana; Emil Robert Kaburuan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
At this time information systems have been widely used by various companies. With the information system, it is hoped that all existing business processes in the company can be helped. However, every newly implemented information system needs an attitude of acceptance from the users in the company, so that the implementation can be successful. As is happening to the government insurance company in Purwasuka (Purwakarta, Subang, Karawang) District. Where the company implements an e-receipt information system that will be used by its employees to record insurance sales. Based on these problems, this paper will analyze the attitudes of application users in the insurance company using TAM. The aspects to be studied are based on perceived usefulness, perceived ease of use, and attitude toward using.  The results of this study show that users give a positive attitude of acceptance.